APPLICATION OF MARKET BASKET ANALYSIS ON HAJI UMAR STORE’S SALES DATA USING THE APRIORI ALGORITHM - Salsabilla Sadedin Nasution; Aninda Muliani Harahap; Adnan Buyung Nasution (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2025)
Science and technology have advanced significantly, leading to an increased reliance on digital information and technology in nearly all aspects of human activity and work, including the micro, small, and medium enterprise (MSME) sector. This study aims to support an MSME, namely Haji Umar Store, in preparing for growing market demands and enhancing its marketing capabilities through the development of a website-based Sales Information System integrated with a Product Recommendation Feature. The research employs a Research and Development (R&D) approach to create a website as the primary product. To implement the Product Recommendation Feature, the study utilizes market basket analysis, a method used to examine consumer purchasing patterns. This analysis is carried out using the Apriori algorithm. The results indicate the identification of 45 valid product combinations that can be utilized in the recommendation feature, providing suggestions when consumers purchase related items.